Comparison of primary maladaptive schemas and attachment styles of women involved in emotional relationships with an age gap of 10 years or less and an age gap of 15 years or more (with male age advantage) - Habibzadeh, Kimia; Rostam Nezhad, Maryam (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The current study aimed to compare early maladaptive schemas and attachment styles in women involved in romantic relationships with an age difference of 10 years or less and an age difference of 15 years or more (with the man being older). Method: This study was causal-comparative in nature; the statistical population comprised 91 individuals, with 50 women involved in romantic relationships with an age difference of 10 years or less (Group One) and 41 women in relationships with an age difference of 15 years or more (Group Two). Participants were selected through convenient and snowball sampling methods and responded to the Hazan and Shaver Attachment Styles Questionnaire (1987) and Young’s 90-item Schema Questionnaire (1990). Data were analyzed using multivariate analysis of variance (MANOVA) with SPSS software. Results: The findings indicated significant differences between the two groups in the anxious/ambivalent attachment style and avoidant attachment style components (P